2016
DOI: 10.1108/hff-07-2014-0237
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the L-PSJA for controlling cylindrical wake flow

Abstract: Purpose – The cylindrical wake flow is an important part of many engineering applications, including wake turbulence, acoustic noise, and lift/drag forces on bodies. The suppression of von Kármán vortex street (VKS) is an important goal for flow control devices. The paper aims to discuss these issues. Design/methodology/approach – The linear plasma synthetic jet actuator (L-PSJA) is utilized as a flow control device to suppress the VKS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Several reviews discussing the VIV problem can be found in review articles (Bearman, 1984;Sarpkaya, 2004;Williamson and Govardhan, 2004). Experimental and numerical studies of the flow around a stationary and forced oscillating circular and square sections to control vortex shedding have been the center of various investigations over many years (Ozgoren, 2006;Mendez and Velazquez, 2007;Sahu and Patnaik, 2011;Singha and Sinhamahapatra, 2011;Prakash Singh et al, 2013;Skote and Ibrahim, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews discussing the VIV problem can be found in review articles (Bearman, 1984;Sarpkaya, 2004;Williamson and Govardhan, 2004). Experimental and numerical studies of the flow around a stationary and forced oscillating circular and square sections to control vortex shedding have been the center of various investigations over many years (Ozgoren, 2006;Mendez and Velazquez, 2007;Sahu and Patnaik, 2011;Singha and Sinhamahapatra, 2011;Prakash Singh et al, 2013;Skote and Ibrahim, 2016).…”
Section: Introductionmentioning
confidence: 99%